Penerapan Algoritme Logika Fuzzy Untuk Dynamic Difficulty Scaling Pada Game Labirin - Ilham Akbar Ahmadi; Eriq Muhammad Adams Jonemaro; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
A majority of new players in a game tend to pick levels at random. This causes an imbalance in the game, which makes the game too easy or too hard. To find out their abilities and levels, input is required from players as a parameter used in the process of determining the difficulty level of a game. In order to address this issue, in this research an implementation of the fuzzy method was utilized for Dynamic Difficulty Scaling to provide a level balance in a labyrinth game. The utilized testing methods were testing of behavior validation and gameplay performance. Behavior validation testing was conducted by requesting 5 volunteers to test the game to see the next level labyrinth output and to analyze the level balance that occurred. The analysis results show that the fuzzy method succeeded in equalizing the soft skills possessed by the players with the level being played. Meanwhile, performance testing was conducted by calculating the number of frames per second (FPS) that are outputted during gameplay. The results show that the best performance was obtained for a map of 5x5 size at 107.22 FPS, while the worst performance was for a labyrinth of 50x50 size at 87.65 FPS. From the results of this performance testing, it can be concluded that the game can be reasonably played, considering that the lower limit for the FPS of a game that can be reasonably played is 30 FPS.